How to be a successful alumni / Priestly Lanting Layang ... [et al.] - Layang, Priestly Lanting; Abang Shamsudin, Dayang Nurul Amieyda; Herman, Nurul Izzah; Standard, Stephanie Sonia; Mokhtar, Muhammad Adib Azfar (Perpustakaan Tun Abdul Razak, 2023)
Graduate school years are unquestionably a stressful and anxiety-inducing time in a person's life. Academic stresses, family and work pressures, and the urge to balance them all are all present. We are aware of how much more challenging everything becomes now that you are earning your degree online. Here are some suggestions to help you strike a balance.